(3efXheI GHf GdTMfI aj Yde GdHdGZIs - (3eMH GdOjf CHh GdhdjO eMeO Hf eMeO Hf GdTMfI,J (B815 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg fSJYjf QH jSQ jG cQje GdMeO ddg hUdi Gddg Ydi QShdg GdPi EUWaGg eMeO hBdg hSdeG hHYO bO CMHHJ Cf CfXeG s
(3BNQgG (B:s
(3HQGYI GdESJgdGd hGdEfJbGd MSf GdNJGe GfJgi GdebGd s
(3HgG fXGe GdJYbjHIs
(3GdejcQhajde ZjQ hGVM JeGekG ai GdJUhjQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdHdGZIs